REVIEW OF DISCOVER ADULTERATION IN SOME COMMON FOODS ITEM BY BIOCHEMICAL QUALITATIVE ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
Food is one most important basic need for all leaving organism, which useful for growth and maintnus. Now day’s foods are contain by different adulterants. Adulteration is a substance which reduces the vital importance of foodstuff. Some of the common adulterants are sugar or jiggery in honey, Starch and melamine in milk, Red lead salts and brick powder in chilli powder, Metanil yellow colours in turmeric powder, Malachite green in vegetable, Mineral oil and castor oils in edible oils, Vanaspati ghee in butter, Lead chromate in pulse, Chalk powder in wheat flour, Prussian blue coloring substances in tea powder, Chicory in coffee powder, Papaya seed in black pepper etc. which is causes various diseases such as epidemic dropsy, glaucoma, cardiac arrest, paralysis, brain damage, anemia, abortion, cancer etc. The aim is to evaluate the presence of adulterant from daily uses food materials like honey, milk , sugar, chilli powder, turmeric powder, green vegetable, edible oil, butter, pulses, wheat flour, tea powder, coffee powder and black pepper which we collected from different local grocery stores and discover food adulterants by biochemical qualitative analysis. The colour change of the sample indicate the according to the reagents is indicates the presence of different adulterants. This information can help to grow the food safety and also people can be aware about the food brands for a healthy life which are very beneficial to our society and our future.